1996
DOI: 10.1128/jvi.70.2.1191-1202.1996
|View full text |Cite
|
Sign up to set email alerts
|

The major transcriptional transactivation domain of simian virus 40 large T antigen associates nonconcurrently with multiple components of the transcriptional preinitiation complex

Abstract: Simian virus 40 (SV40) large T antigen (Tag) is a promiscuous transcriptional transactivator; however, its mechanism of transactivation remains unknown. Recent studies have suggested the possible involvement of protein-protein interactions with TBP, the TATA box-binding protein of TFIID, and TEF-1, an enhancerbinding factor. We show here that (i) the Tag domain containing amino acids 133 to 249 directly interacts with the general transcription factor TFIIB, the activator protein Sp1, and the 140-kDa subunit of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
28
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 67 publications
(124 reference statements)
2
28
0
Order By: Relevance
“…A large number of activities reside in or are dependent on the N-terminal 250 amino acids of T antigen. These include binding the cellular proteins of the retinoblastoma (Rb) susceptibility family (Rb/p130/p107) (8,(11)(12)(13), a protein of unknown function (p185) (23), the heat shock 73 (Hsc73) protein (38), and the transcription factors TFIIB, Sp1, TBP, TEF-1, and the 140K subunit of RNA polymerase (2,19), as well as the nuclear localization signal (21); binding to the viral origin of replication (1); activities needed for maximal stimulation of cell DNA synthesis (9,10); and transcriptional transactivating activities (24-26, 36a, 49). Thus, it is not clear which one or several of these activities are needed to confer the altered growth properties.…”
mentioning
confidence: 99%
“…A large number of activities reside in or are dependent on the N-terminal 250 amino acids of T antigen. These include binding the cellular proteins of the retinoblastoma (Rb) susceptibility family (Rb/p130/p107) (8,(11)(12)(13), a protein of unknown function (p185) (23), the heat shock 73 (Hsc73) protein (38), and the transcription factors TFIIB, Sp1, TBP, TEF-1, and the 140K subunit of RNA polymerase (2,19), as well as the nuclear localization signal (21); binding to the viral origin of replication (1); activities needed for maximal stimulation of cell DNA synthesis (9,10); and transcriptional transactivating activities (24-26, 36a, 49). Thus, it is not clear which one or several of these activities are needed to confer the altered growth properties.…”
mentioning
confidence: 99%
“…LT, an essential viral replication factor, can regulate viral early and late transcription in SV40 infection (Khoury & May 1977;Hansen et al 1981;Alwine & Picardi 1986). LT also serves as a transcriptional activator of cellular promoters through direct interaction with components of transcription machines including TBP, TAPs and more to regulate cellular or viral transcription (Johnston et al 1996). Combined with the ability to inhibit p53, LT is able to drive cells into the S phase (Sladek et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that large T antigen can regulate cell growth, in part, by binding and inactivating the tumor suppressors proteins pRB and p53 42,43 . In addition, large T antigen can transactivate cellular genes, and this process is mediated by specific protein–protein interactions with multiple components of the transcription machinery 44–47 . These alterations in the transcriptional activity of specific cellular genes most likely play an important role in the growth‐promoting activity induced by large T antigen.…”
Section: Discussionmentioning
confidence: 99%